Proptosis, Micrognathia, Low Set Ear and Chest Deformity in a Patient with Extra Marker Chromosome 22 - Asieh Mosallanejad; Fatemeh Sayarifard; Sima Hosseinverdi; Farzaneh Abbasi; Hosein Shabni Mirzaee; Nima Rezaei (Acta Medica Iranica, 2015)
There is a number of syndromes, associated with proptosis, micrognathia, low-set ear and chest deformity. Herein, we report a 9-year-old female with such phenotype who was presented with a vaginal neuroma. The result of karyotype showed 47XX, with extra marker chromosome 22. Although such a manifestation had not been reported in the literature, it should be considered as a very rare manifestation of the disease.